Applied numerical methods with MATLAB for engineers and scientists - Chapra, Steven C. (New York, NY McGraw Hill LLC, 2023)
"This book is designed to support a one-semester course in numerical methods. It has been written for students who want to learn and apply numerical methods in order to solve problems in engineering and science. As such, the methods are motivated by problems rather than by mathematics. That said, sufficient theory is provided so that students come away with insight into the techniques and their shortcomings"--Provided by publisher.
Mathematical modeling, numerical methods, and problem solving -- MATLAB fundamentals -- Programming with MATLAB -- Roundoff and truncation errors -- Roots : bracketing methods -- Roots : open methods -- Optimization -- Linear algebraic equations and matrices -- Gauss elimination -- Lu factorization -- Matrix inverse and condition -- Iterative methods -- Eigenvalues -- Linear regression -- General linear least-squares and nonlinear regression -- Fourier analysis -- Polynomial interpolation -- Splines and piecewise interpolation -- Numerical integration formulas -- Numerical integration of functions -- Numerical differentiation -- Initial-value problems -- Adaptive methods and stiff systems -- Boundary-value problems.
Includes bibliographical references and index.
Keywords: MATLAB -- Textbooks; Numerical analysis -- Data processing -- Textbooks; Engineering mathematics -- Textbooks